Active drag and physical characteristics in age group swimmers - Corrêa, S. C.; Alves, F.; Botelho, A.; Rama, L.; Martins-Silva, A. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
The purpose of this study was to identify the influence of body size and morphology in active drag (Da) in front crawl swimming. Seventeen male national level swimmers (age: 15.42 ± 0.53 years, height: 178.52 ± 7.42 cm, body mass: 66.82 ± 7.45 kg) were selected from a large pool (350) of swimmers evaluated using the velocity perturbation method. Inclusion criterion was having achieved the same maximal velocity in the test (1.78 m.s-1). Hydrodynamic variables showed large variation and were correlated to body mass and height. Height corrected for the squared body mass showed a strong negative association with Da (-0.810). Swimmers of equivalent performance level have different active hydrodynamic profiles, according to body size and morphological characteristics.